Monitoring and Analysis on Eutrophication Status in Baoan Lake of Hubei Province - Xu Xiaohui; Liu Hui; Wang Weimu; Chen Jiaxin; Xia Jihong (Shuitu baochi tongbao)
[Objective] The spatio-temporal characteristics of the eutrophication status in Baoan Lake, and the key water environmental impact factors were studied in order to provide a basis for ecological restoration and protection. [Methods] Monitoring sites were set up in Baoan Lake. Sampling and monitoring were conducted from 2019 to 2021. The trophic state index (TLI) was introduced to evaluate the nutritional status of the lake, and spatial autocorrelation analysis was used to study the spatial correlation and aggregation degree of eutrophication in Baoan Lake. The main water environmental impact factors of chlorophyll a concentration were analyzed by a logit model. [Results] The nutrient status of Baoan Lake fluctuated between mesotrophic and slightly eutrophic, and the range of TLI was 47.25~55.86. The eutrophication level of Baoan Lake showed significant spatial autocorrelation, with Global Moran's I values of 0.46, 0.93, 0.60, 0.31, 0.60, and 0.62. The southern areas of the main boady of Baoan Lake were the hot spots (high/high concentration) for lake eutrophication level (p<0.01), and Biandantang lake area was the cold spot (low/low concentration) for lake eutrophication level (p<0.01). The main water environmental factors affecting the change of chlorophyll a concentration were transparency >TP >pH value >CODMn >water depth >DO, which were significantly correlated with chlorophyll a concentration. [Conclusion] The eutrophication status of Baoan Lake water is good. Further improvement in the water nutritional status of Baoan Lake can be achieved by controlling the agricultural non-point source pollution, strengthening the management of rivers, regulating water level, recovering aquatic vegetation, and so on.